DESCRIPTION OF FOOD HYGIENE SANITATION IN FOODCOURT CANTEEN OF THE UNIVERSITY MUHAMMADIYAH JAKARTA - Temaspraba, Nadhifah Salsabila; Munaya Fauziah; Nurmalia Lusida; Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Food hygiene has an important role in ensuring that the food consumed is safe and healthy so that you can avoid illness. Based on the annual report of the Center for Drug and Food Data and Information in 2019, there were 6,205 data on poisoning cases. The most common causes of poisoning based on food were household processed foods (265 cases), processed catering services (97 cases), and processed snacks (43 cases). This study aimed to find out the description of the hygiene and sanitation of street food in the food court canteen at the University of Muhammadiyah Jakarta. This research is a qualitative descriptive research with in-depth interviews and observation methods. The research location is in the food court canteen at the University of Muhammadiyah Jakarta. The independent variables studied were food handlers, equipment, water, foodstuffs, additives, serving, vendor suggestions, and traders' centers. The informants in this study were 10 snack food vendors, 1 person in charge of the canteen, and 1 cleaning officer. The results of this study are that the hygiene and sanitation behavior of food handlers is good, but food sellers are still not disciplined in using aprons. The equipment used is always cleaned and kept in a clean place. The use of water, food ingredients, and additives is by the requirements, but in the process of serving the food served is not covered or does not use a cover. Vendors' facilities and traders' centers are good and overall meet the requirements of Kepmenkes No. 942 of 2003. The weight assessment was also carried out and the result was 86%.